A&T Bangladesh Follow-up Survey 2016: Community - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the follow-up community survey conducted in 2016 to collect data on the sustained impacts of A&T’s behavior change communication interventions on infant and young child feeding (IYCF) practices in Bangladesh which include: 1) Sustained impact on IYCF practices and knowledges, 2) Expansion of program exposure and promoted practices into new areas, and 3) Diffusion of IYCF information. A&T is a global initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding and complementary feeding practices. During Phase 1 (A&T-1, 2009-2014), A&T Bangladesh were designed to support improvements in IYCF primarily by improving policy and regulatory environments (advocacy) and shaping IYCF demand and practice (community-based interventions and mass media). In 2014, IFPRI in collaboration with Data Analysis and Technical Assistance (DATA) conducted the endline survey. The overall findings of the impact evaluation indicated that A&T’s work in Bangladesh is a remarkable success story of scaling up what has been challenging to date in the field of nutrition: complex, high intensity and at-scale behavior change communication interventions. Since the termination of A&T-1 project support in 2014, BRAC has continued to deliver interpersonal counseling on IYCF through its cadres of frontline health workers to over 90% of the country (456 out of 490 upazilas) with the support of other external donor funds, with several additional modifications (e.g. added focus on maternal nutrition, less frequent training and supervision, and reduced performance based incentives). In 2016, a follow-up study was conducted to examine the sustained impact on IYCF practices, expansion of program exposure and promoted practices into new areas, and diffusion of IYCF information. Because achievements related to service delivery and outcomes were intended to be sustained in the A&T-1 intensive areas and later expanded to other areas where BRAC’s Essential Health Care program operates, including the A&T-1 comparison or non-intensive areas (described further in the next section), the study aimed to examine elements in both the original A&T intensive and A&T non-intensive areas. The follow-up survey consisted of two questionnaires: 1) community, and 2) household/mother survey and was conducted between April and June of 2016. A census form was applied to each village in order to capture administrative information on household location, household composition, and literacy and main occupations of all household members. The form also identified households with children 0-24 months of age, to generate the on-site household sampling list. The follow-up study was conducted in the same 20 rural subdistricts using a similar design to the original impact evaluation design. The purpose of the community questionnaire was to gather data on underlying factors at the community level, for comparing the different clusters over time. The community questionnaire captured the factors influencing suboptimal feeding practices that are embedded within the larger society and environment. Specifically, the community questionnaire was designed to provide information on the following aspects of each village: 1) General characteristics: population, proportions of minority and poor households, main sources of income in peak and low seasons, 2) Infrastructure: access to main road, electricity, gas, and irrigation systems, 3) Distance to/from the nearest major town, types of transportation used to reach this town, 4) Natural disasters occurred in the village during the last year, and 5) Presence of organizations or support groups and nutrition programs/projects.